Echocardiography as a Simple Test to Detect Diastolic Dysfunction in Normotensive Diabetes Mellitus Patients - Tamrakar, Dhiraj; Lopchan, Rupa; Adhikari, Suman; Shrestha, Tulsi Ram (Medical Journal of Eastern Nepal, 2023)
Background: Diabetes mellitus may develop left ventricular diastolic dysfunction which may cause diabetic cardiomyopathy even in the absence of atherosclerosis. The aim of our study is to look for the prevalence of diastolic dysfunction in diabetes mellitus patients with normal blood pressure.Methods: Our study was cross sectional which included 50 patients who were normotensive diabetic with no evidence of coronary artery disease, thyroid or renal disease. 2D echocardiography was done to look for LVDD and its prevalence.Results: LVDD was present in 32 patients (64%). It was found more in the females as compared to men and more in the 60-79 years age.There was more number of patients with diastolic dysfunction in those with more years of diabetes duration. It was also found that LVDD was more in those with HbA1c of 6.5% or more.Conclusion: LVDD cause heart failure in diabetic patients. Thus, echocardiography is a simple noninvasive method to detect diabetic cardiomyopathy.